Effect of climate change on bud phenology of young aspen plants (Populus tremula. L). Issue 19 (1st September 2017) - Sivadasan, Unnikrishnan; Randriamanana, Tendry; Chenhao, Cao; Virjamo, Virpi; Nybakken, Line; Julkunen‐Tiitto, Riitta
Abstract: Boreal tree species are excellent tools for studying tolerance to climate change. Bud phenology is a trait, which is highly sensitive to environmental fluctuations and thus useful for climate change investigations. However, experimental studies of bud phenology under simulated climate change outdoors are deficient. We conducted a multifactorial field experiment with single (T, UVA, UVB) and combined treatments (UVA+T, UVB+T) of elevated temperature (T, +2°C) and ultraviolet‐B radiation (+30% UVB) in order to examine their impact on both male and female genotypes of aspen ( Populus tremula L.). This study focuses on the effect of the treatments in years 2 and 3 after planting (2013, 2014) and follows how bud phenology is adapting in year 4 (2015), when the treatments were discontinued. Moreover, the effect of bud removal was recorded. We found that elevated temperature played a key role in delaying bud set and forcing bud break in intact individuals, as well as slightly delaying bud break in bud‐removed individuals. UVB delayed the bud break in bud‐removed males. In addition, both UVA and UVB interacted with temperature in year 3 and even in year 4, when the treatments were off, but only in male individuals. Axillary bud removal forced both bud break and bud set under combined treatments (UVA+T, UVB+T) and delayed both under individual treatments (T, UVB). In conclusion, male aspens were more responsive to the treatments than females and that effect of elevated temperature and UV radiation on bud set and bud break of aspen is not disappearing over 4‐year study period. Abstract : Buds play an important role in the growth and development of plants. Plant growth and dormancy depicted by the initial response are seen in buds. This makes them an important tool for visualizing the expected climate change impacts.